Proposing a linguistic repertoires perspective in multilingual higher education contexts - Melike Bulut Albaba (Journal of Learning Development in Higher Education)
Anglophone Higher Education Institutions have embraced cultural diversity but continue to approach linguistic diversity through a deficit perspective, often treating multilingualism as an obstacle rather than a resource (Preece et al., 2018). This paper argues for the adoption of a linguistic repertoires perspective in learning development to leverage students' full linguistic capacities, thereby enhancing cognitive engagement, fostering inclusivity, and contributing to the decolonisation of academic spaces. Drawing on Cummins (2007), I explore how linguistic repertoires function as cognitive tools, aiding comprehension and critical thinking. Additionally, insights from Park and May (2025) and Preece (2019b) illustrate how integrating linguistic repertoires in learning development promotes inclusion and challenges linguistic discrimination. Finally, inspired by Wei and García (2022), I position linguistic repertoires as central to a decolonising agenda in higher education. I call upon learning developers to create pedagogical frameworks that recognise linguistic diversity as an asset, facilitating equitable and enriched educational experiences.